Sheath fluid impacts the depletion of cellular metabolites in cells afflicted by sorting induced cellular stress (SICS) - Ryan, Kamilah; Rose, Rebecca E.; Jones, Drew R.; Lopez, Peter A. (Cytometry. Part A, 2021)
Flow cytometrists have long observed a spectrum of cell‐type‐specific changes ranging from minor functional defects to outright cell destruction after purification of cells using conventional droplet cell sorters. We have described this spectrum of cell perturbations as sorter induced cellular stress, or SICS (Lopez and Hulspas, Cytometry, 2020, 97, 105–106). Despite the potential impact of this issue and ubiquitous anecdotes, little has been reported about this phenomenon in the literature, and the underlying mechanism has been elusive. Inspired by others' observations (Llufrio et al., Redox Biology, 2018, 16, 381–387 and Binek et al., Journal of Proteome Research, 2019, 18, 169–181), we set out to examine SICS at the metabolic level and use this information to propose a working model. Using representative suspension (Jurkat) and adherent (NIH/3T3) cell lines we observed broad and consistent metabolic perturbations after sorting using a high‐speed droplet cell sorter. Our results suggest that the SICS metabolic phenotype is a common cell‐type‐independent manifestation and may be the harbinger of a wide‐range of functional defects either directly related to metabolism, or cell stress response pathways. We further demonstrate a proof of concept that a modification to the fluidic environment (complete media used as sheath fluid) in a droplet cell sorter can largely rescue the intracellular markers of SICS, and that this rescue is not due to a contribution of metabolites found in media. Future studies will focus on characterizing the potential electro‐physical mechanisms inherent to the droplet cell sorting process to determine the major contributors to the SICS mechanism.